Kazakhstan : Public Expenditure and Institutional Review for the Agricultural Sector - World Bank Group (World Bank, Washington, DC, 2017)
Agriculture occupies a key position in the Kazakhstan economy. Although accounting for only 5 percent of GDP, agriculture continues to employ almost one third of the population. Studies of agriculture in Kazakhstan confirm significant un-tapped productive and export potential for the sector. Accordingly, agriculture and the related industries have become a major priority in the Government’s initiatives for promoting economic development and diversification, including the 30 Corporate Leaders program and the Industrial Map of Kazakhstan. Improving the impact of budgetary policies in agriculture represents a key objective for the successful transformation of the sector. This includes both increasing the efficiency of existing expenditures and restructuring those expenditures with the goal of enhancing productivity and competiveness. This is therefore, an opportune time for critical review of budgetary expenditures and policies in agriculture.